A pilot study on simultaneous stimulation of the primary motor cortex and supplementary motor area using gait-synchronized rhythmic brain stimulation to improve gait variability in post-stroke hemiparetic patients - Yamashita, Kazuma; Ida, Ruido; Koganemaru, Satoko; Horiba, Mitsuya; Nojima, Ippei; Mima, Tatsuya; Ono, Yumie; Shibata, Sumiya; Hosoe, Takuya; Tachiwa, Hiromasa; Yamashita, Hiroaki; Itoh, Akihiro; et al. (Frontiers in Human Neuroscience, 2025)
IntroductionGait impairment is a common and disabling consequence of stroke. While walking speed is a key indicator of recovery, gait variability is closely associated with fall risk and long-term functional decline. Previous studies have suggested that functional interaction between the supplementary motor area (SMA) and primary motor cortex (M1) plays a key role in post-stroke gait control. Rather than stimulating these regions independently, simultaneous activation of the SMA—critical for rhythm modulation and motor planning—and gait-synchronized stimulation of the M1—essential for motor execution—may offer enhanced benefits for gait stability.ObjectiveTo assess the feasibility, safety, and preliminary effects of a combined brain stimulation intervention targeting the SMA and M1 on gait variability and balance in individuals with post-stroke hemiparesis.MethodsSixteen individuals with stroke within 180 days after the onset, aged 40–90 years, who were able to walk on a treadmill were recruited in this study of multi-center, randomized, controlled pilot trial with a parallel-group design. Participants were randomly allocated to either an intervention group (n = 8) receiving 20 min of simultaneous transcranial direct current stimulation (tDCS) to the SMA and gait-synchronized rhythmic stimulation to the M1 during treadmill walking, or to a control group (n = 8) receiving sham stimulation. Both groups underwent 15 sessions of walking practice over 3 weeks. Primary outcomes were feasibility indicators including recruitment, retention, adherence and adverse events and preliminary estimates of effect on gait variability such as coefficient of variation for stride, stance, and swing times on the paretic side. Balance was assessed using the Mini-Balance Evaluation Systems Test (Mini-BESTest).ResultsAll 16 participants completed the intervention without adverse events, indicating high feasibility. The intervention group showed significantly reduced stride time variability on the paretic side and improved Mini-BESTest scores compared to the control group. A significant correlation was observed between reductions in gait variability and improvements in balance.ConclusionsThis pilot trial supports the feasibility and safety of a combined SMA and M1 stimulation approach. Preliminary findings suggest potential benefits in reducing gait variability and improving balance after stroke, warranting further investigation in a definitive trial.